Pressure ulcer summit 2018: An interdisciplinary approach to improve our understanding of the risk of pressure‐induced tissue damage. Issue 5 (11th June 2019) - Gould, Lisa J.; Bohn, Gregory; Bryant, Ruth; Paine, Tim; Couch, Kara; Cowan, Linda; McFarland, Frances; Simman, Richard
Abstract: Pressure ulcers (PrUs) affect approximately 2.5 million patients and account for 60, 000 deaths annually. They are associated with an additional annual cost of $43, 000 per related hospital stay and a total cost to the US health care system as high as $25 billion. Despite the implementation of national and international PrU prevention guidelines and toolkits, rates of facility‐acquired PrU s and PrUs in people with spinal cord injury are still high. A new paradigm is needed that distinguishes between prevention and treatment research methods and includes not only the causative factors of pressure and tissue deformation but also patient‐specific anatomical differences and the concomitant biological cellular processes, including reperfusion injury, toxic metabolites, ischemia, cell distortion, impaired lymphatic drainage, and impaired interstitial fluid flow that compound existing tissue damage. The purpose of this article is to summarize the highlights from the first annual Pressure Ulcer Summit held February 9–10, 2018 in Atlanta, Georgia (sponsored by the Association for the Advancement of Wound Care in partnership with multiple professional organizations). This international, interdisciplinary summit brought together key stakeholders in wound care and PrU prevention and management to highlight advances in pathophysiology of pressure‐induced tissue damage; explore challenges in current terminologies, documentation, and data collection; describe innovations in clinical care; and identify research opportunities to advance the science of PrU prevention and management.